Advances in Intelligent Systems and Applications - Volume 1 Proceedings of the International Computer Symposium ICS 2012 Held at Hualien, Taiwan, December 12-14, 2012 - Chang, Ruay-Shiung; Jain, Lakhmi C.; Peng, Sheng-Lung (Smart Innovation, Systems and Technologies,, 2013)
The field of Intelligent Systems and Applications has expanded enormously during the last two decades. Theoretical and practical results in this area are growing rapidly due to many successful applications and new theories derived from many diverse problems. This book is dedicated to the Intelligent Systems and Applications in many different aspects. In particular, this book is to provide highlights of the current research in Intelligent Systems and Applications. It consists of research papers in the following specific topics:   l   Graph Theory and Algorithms l   Interconnection Networks and Combinatorial Algorithms l   Artificial Intelligence and Fuzzy Systems l   Database, Data Mining, and Information Retrieval l   Information Literacy, e-Learning, and Social Media l   Computer Networks and Web Service/Technologies l   Wireless Sensor Networks l   Wireless Network Protocols l   Wireless Data Processing   This book provides a reference to theoretical problems as well as practical solutions and applications for the state-of-the-art results in Intelligent Systems and Applications on the aforementioned topics. In particular, both the academic community (graduate students, post-doctors and faculties) in Electrical Engineering, Computer Science, and Applied Mathematics; and the industrial community (engineers, engineering managers, programmers, research lab staffs and managers, security managers) will find this book interesting.